2012
DOI: 10.1016/s1470-2045(12)70121-3
|View full text |Cite
|
Sign up to set email alerts
|

Focal therapy for localised unifocal and multifocal prostate cancer: a prospective development study

Abstract: SummaryBackgroundRadical whole-gland therapy can lead to significant genitourinary and rectal side-effects for men with localised prostate cancer. We report on whether selective focal ablation of unifocal and multifocal cancer lesions can reduce this treatment burden.MethodsMen aged 45–80 years were eligible for this prospective development study if they had low-risk to high-risk localised prostate cancer (prostate specific antigen [PSA] ≤15 ng/mL, Gleason score ≤4 + 3, stage ≤T2), with no previous androgen de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
235
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 355 publications
(245 citation statements)
references
References 32 publications
5
235
0
5
Order By: Relevance
“…Medium to long-term outcomes of modern techniques are not yet available [130,131], but short-term outcomes appear favourable for selected men in recent studies [132], especially those where mpMRI was used together with template mapping biopsy [133]. The key to a successful outcome with focal therapy lies in the accurate localisation and risk stratification of all foci of clinically significant cancer.…”
Section: Mri In T-staging Treatment Selection and Planningmentioning
confidence: 99%
“…Medium to long-term outcomes of modern techniques are not yet available [130,131], but short-term outcomes appear favourable for selected men in recent studies [132], especially those where mpMRI was used together with template mapping biopsy [133]. The key to a successful outcome with focal therapy lies in the accurate localisation and risk stratification of all foci of clinically significant cancer.…”
Section: Mri In T-staging Treatment Selection and Planningmentioning
confidence: 99%
“…[9][10][11][12][13] In previous studies, complications reported included the rate of bladder outlet obstruction, urinary incontinence and erectile dysfunction, and their incidence was 0-5.0%, 0-10% and 5.0-6.0%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Proton-beam prostate treatment fortunately remains uncommon, but new facilities are proliferating rapidly, and because once a facility is constructed there is a major incentive to recoup a prodigious investment, local prostate cancer practice patterns tend to shift to reflect more use of proton-beam treatment. 7 The other recent paper, from Ahmed et al, 8 reported MRI-guided focal treatment with high-intensity focused ultrasound www.nature.com/nrclinonc NEWS & VIEWS (HIFU). HIFU has been the subject of multiple series, mostly in Europe.…”
mentioning
confidence: 99%
“…Ahmed et al 8 reported on 42 men with low-risk to intermediate-risk prostate cancer treated with HIFU targeting areas of cancer based on biopsy and imaging. The protocol allowed up to 60% ablation of the prostate, and required transperineal template prostate biopsies under anaes thesia before and after therapy.…”
mentioning
confidence: 99%
See 1 more Smart Citation